FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY DI INDONESIA - , NINA YULIANASARI, SE., Dr. Eko Suwardi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Audit delay is the time span measured by the length of the day in completing the audit process by independent auditors of the closing date of December 31, until the date stated in the report of independent auditors. The purpose of this study was to determine the effect of firms size, profitability, solvency levels, KAP size, and auditor's opinion on the audit delay. The object of this research is the financial statements of companies listed in Bursa Efek Indonesia (BEI) from years 2007 to 2009. So that samples obtained as many as 260 companies. The method used in this study is by descriptive statistical methods, classical assumption and hypothesis testing. Based on the classic assumption test results of this study there were no symptoms of normality model, multicollinearity, autocorrelation and heteroscedasticity. Based on the hypothesis test with a multiple linear regression that is testing the F note that firms size, profitability, solvability level, KAP size, and auditor opinion simultaneously affect the audit delay. While the results of t test is known only firms size, KAP size, and auditor opinions that influence the audit delay, while the level of profitability and solvency of no significant impact on audit delay. To obtain the determinant coefficient of 0.095 which means 9.5% dependent variable (audit delay), influenced by independent variables (firm size, profitability, solvency levels, kap size, and auditor's opinion), while 90.5% are influenced by other variables.